Synthesis of some novel annulated pyrido[2,3-d]pyrimidines via stereoselective intramolecular hetero Diels–Alder reactions of 1-oxa-1,3-butadienes - Deb, Mohit L.; Bhuyan, Pulak J. (Beilstein Journal of Organic Chemistry, 2010)
Some novel annulated pyrido[2,3-d]pyrimidines 6 and 7 were synthesized stereoselectively by intramolecular hetero Diels–Alder reactions involving 1-oxa-1,3-butadienes.
Keywords: β-halo aldehydes; hetero Diels–Alder reaction; 1-oxa-1,3-butadiene; pyrido[2,3-d]pyrimidines; uracil